Application of interface material and effects of oxygen gradient on the performance of single-chamber sediment microbial fuel cells (SSMFCs) - Wang, Chin Tsan; Sangeetha, Thangavel; Yan, Wei Mon; Chong, Wen Tong; Saw, Lip Huat; Zhao, Feng; Chang, Chung Ta; Wang, Chen Hao (Elsevier, 2019)
Single-chamber sediment microbial fuel cells (SSMFCs) have received considerable attention nowadays because of their unique dual-functionality of power generation and enhancement of wastewater treatment performance. Thus, scaling up or upgrading SSMFCs for enhanced and efficient performance is a highly crucial task. Therefore, in order to achieve this goal, an innovative physical technique of using interface layers with four different pore sizes embedded in the middle of SSMFCs was utilized in this study. Experimental results showed that the performance of SSMFCs employing an interface layer was improved regardless of the pore size of the interface material, compared to those without such layers. The use of an interface layer resulted in a positive and significant effect on the performance of SSMFCs because of the effective prevention of oxygen diffusion from the cathode to the anode. Nevertheless, when a smaller pore size interface was utilized, better power performance and COD degradation were observed. A maximum power density of 0.032 mW/m2 and COD degradation of 47.3% were obtained in the case of an interface pore size of 0.28 μm. The findings in this study are of significance to promote the future practical application of SSMFCs in wastewater treatment plants.